Pirfenidone facilitates immune infiltration and enhances the antitumor efficacy of PD-L1 blockade in mice. (1st January 2020) - Qin, Wan; Zou, Jun; Huang, Yongbiao; Liu, Chaofan; Kang, Yalin; Han, Hu; Tang, Yang; Li, Long; Liu, Bo; Zhao, Weiheng; Yuan, Xianglin
ABSTRACT: Idiopathic pulmonary fibrosis (IPF) patients have a high risk of developing lung cancer, with few treatment options available. Pirfenidone, an antifibrotic agent approved for the treatment of IPF, has been demonstrated to suppress the TGFβ signaling and modulate the expression of immune-related genes. However, for lung cancer patients with comorbid IPF, whether pirfenidone has any synergetic effect with immune checkpoint inhibitors has not been investigated. In this study, we showed that pirfenidone monotherapy attenuated tumor growth with an increased T cell inflammatory signature in tumors. Co-administration of pirfenidone with PD-L1 blockades significantly delayed the tumor growth and increased survival, compared with the effect of either treatment alone. Combination therapy promoted gene expression with a unique signature associated with innate and adaptive immune response resulted in the infiltration of immune cells and optimal T cell positioning. Furthermore, we showed a great benefit of combination therapy in alleviating the pulmonary fibrosis and reducing the tumor growth in a tumor-fibrosis model. Our results collectively demonstrated that pirfenidone facilitated antitumor immunity and enhanced the efficacy of PD-L1 blockades. It may act as an adjuvant to immunotherapy in cancer treatment, particularly, in lung cancer patients with preexisting IPF.